(untitled) (Annals of the Institute of Biology, 2023)
Carex acuta leaves were sampled on the edge of the glacial lake Gornje bare (National Park “Sutjeska”, Zelengora mountain, Bosnia and Herzegovina). Two types of samples were taken: plants that grew on moist soil at the time of sampling, designated as CAm, and plants that grew partially submerged at the time of sampling were designated as CAs. Our work aimed to compare the content of photosynthetic pigments, concentration of total phenolic compounds and flavonoids as well as antioxidant capacity between two CAm and CAs samples. Our results showed that the concentration of total chlorophyll and carotenoids were higher in the CAm sample. Higher concentrations of phenolic compounds (28.987± 0.502 mg/g DW) and flavonoids (22.079 ± 1.471 mg/g DW) were measured in CAs samples. The antioxidant capacity measured by the ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) method and phosphomolybdenum method were higher in CAm extract. The abilities to reduce Fe3+ ions and to chelate Fe were higher for CAs samples. Obtained results indicate that the content of phenolic compounds and the antioxidant capacity of plants are significantly influenced by environmental conditions even for the same species. The present study provides the first insight into the antioxidant characteristics of C. acuta from the western Balkans.